2021
DOI: 10.47678/cjhe.vi0.188965
|View full text |Cite
|
Sign up to set email alerts
|

What matters more? What matters less? Changes in the transition to post-secondary between two Toronto high-school cohorts

Abstract: Using data from two Toronto student cohorts that entered high school five years apart, this study uses descriptive and multivariate techniques to examine short-term change in the predictors of four possible pathways after high school: confirming a place in university, confirming a place in college, applying but no admittance, or not applying at all. From a comparative cohort perspective, the analysis considers various overlapping ascriptive and school experience factors that contribute to unequal transitions—f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Findings revealed differential postsecondary preparation and postsecondary outcomes for students based on both gender and race. The findings highlight the importance of transition researchers seeking to understand marginalized students' intersecting identities (Robson et al, 2018). Furthermore, intersectionality theory necessitates moving beyond only looking at the interaction of personal factors (e.g., race, disability, sex; Crenshaw & Gotanda, 1995).…”
Section: Conceptual Foundations: Advancing Critical Theories In Trans...mentioning
confidence: 97%
See 1 more Smart Citation
“…Findings revealed differential postsecondary preparation and postsecondary outcomes for students based on both gender and race. The findings highlight the importance of transition researchers seeking to understand marginalized students' intersecting identities (Robson et al, 2018). Furthermore, intersectionality theory necessitates moving beyond only looking at the interaction of personal factors (e.g., race, disability, sex; Crenshaw & Gotanda, 1995).…”
Section: Conceptual Foundations: Advancing Critical Theories In Trans...mentioning
confidence: 97%
“…It is worth noting that other studies using critical theories have reported similar findings about the experiences of racially and ethnically marginalized youth. For example, grounded in intersectionality theory, Robson et al, (2018) investigated the transition to postsecondary education of cohorts of 12 th -grade students with a particular focus on the intersection of race and gender. Findings revealed differential postsecondary preparation and postsecondary outcomes for students based on both gender and race.…”
Section: Conceptual Foundations: Advancing Critical Theories In Trans...mentioning
confidence: 99%
“…Instead of race, national data sets have often measured immigrant status or if a respondent is a member of a "visible minority." As argued elsewhere, visible minority status is a problematic conceptualization of race which, among other things, centers whiteness (Robson et al, 2021b). For example, in 2016 less than half of the Toronto population self-identified as white (City of Toronto, 2019).…”
Section: Introductionmentioning
confidence: 99%